Concept Selection and Cost Calculation for A Ball Machine Used in Training Goalkeepers - Nicolae TUNSOIU; Cristian-Vasile DOICIN; Daniela TUNSOIU; Roman MURZAC; Mihaela-Elena ULMEANU (Communications of International Proceedings, 2021)
Sport is a physical activity, performed with the assistance of a trained coach, that helps people to stay fit. Depending on the type of sports activity, people can practice competitive sports or do it as a hobby. Competitive sports are performed with the help of specialized equipment that are used by players during training or official matches. The most popular sports are ball games including football, handball, volleyball, golf, basketball etc. Football is one of the most popular sports practiced in the world. Performances of athletes are reviewed all the time, followed by many trainings led by their coaches. To reduce the effort made by the coach and improve the player’s performance, special equipment which throws the ball on a certain trajectory and a specific speed. This paper analyses the needs and requirements for a ball throwing machine and presents different concepts for future development. The methodology of needs analysis and decision for the optimal concept is presented in detail. Based on the optimum selection, the economic analysis of the chosen concept is performed, and the total cost of the product is calculated. Cost-effective manufacturing is analyzed for additive manufacturing technologies applied for target components. These additive technologies allowed the optimization of internal structures of parts, to better suit customer and manufacturing requirements.
Keywords: Sports; Equipment; Cost; Concept Development